Notes on the concept of political crime in the 1988 Federal Constitution and crimes against the Democratic Rule of Law (Revista do Tribunal Regional Federal da 3ª Região, 2023)
The present work deals with the possible concepts of political crime in the Federal Constitution, through the analysis of its historical evolution, species and respective theories. In addition, it aims to investigate the nature of a political offense or not of crimes against the Democratic State of Law, successors of the criminal types provided for in the repealed National Security Law. The methodology will consist of a qualitative analysis of the Federal Constitution and of infraconstitutional laws, as well as doctrine and jurisprudence of the Federal Supreme Court about political crime. Regarding crimes against the Democratic State of Law, still very recent in the legal system, the two positions already established in the doctrinal scope regarding their nature will be examined, concluding that these crimes must be considered political, with the exceptions provided for in the legislation.
Keywords: Political crime; Constitution; Democratic State of Law